2021
DOI: 10.3389/fmicb.2021.769304
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the Right Life Partner: Ecological Drivers of Lichen Symbiosis

Abstract: Lichens are an iconic example of symbiotic systems whose ecology is shaped by the requirements of the symbionts. Previous studies suggest that fungal (mycobionts) as well as photosynthesizing (phycobionts or cyanobionts) partners have a specific range of acceptable symbionts that can be chosen according to specific environmental conditions. This study aimed to investigate the effects of climatic conditions and mycobiont identity on phycobiont distribution within the lichen genera Stereocaulon, Cladonia, and Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 81 publications
0
19
0
Order By: Relevance
“…The final dataset included 241 sequences, of which 205 were newly produced (51 sequences of mycobiont ITS rDNA, 30 of cox1, 29 of EF-1α, 27 of mtSSU, 32 of RPB2, 33 sequences of photobiont ITS rDNA and three of photobiont actin type I gene), 15 were retrieved from our previous datasets [55,56] and 21 downloaded from GenBank (https: //www.ncbi.nlm.nih.gov/ (accessed on 25 November 2021)). The newly obtained sequences have been deposited in GenBank (see Supplementary Table S1 for accession numbers).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final dataset included 241 sequences, of which 205 were newly produced (51 sequences of mycobiont ITS rDNA, 30 of cox1, 29 of EF-1α, 27 of mtSSU, 32 of RPB2, 33 sequences of photobiont ITS rDNA and three of photobiont actin type I gene), 15 were retrieved from our previous datasets [55,56] and 21 downloaded from GenBank (https: //www.ncbi.nlm.nih.gov/ (accessed on 25 November 2021)). The newly obtained sequences have been deposited in GenBank (see Supplementary Table S1 for accession numbers).…”
Section: Resultsmentioning
confidence: 99%
“…For example, C. polydactyla/umbricola, which commonly grow on dead wood among bryophytes in humid forests, is associated with A. italiana , which has previously been reported from Stereocaulon and Cladonia spp. in relatively humid and stable climates [ 55 , 58 ]. Similarly, A. irregularis , which is restricted to cold areas of the northern hemisphere [ 26 ], was one of the associated photobionts of C. bellidiflora , which usually occurs on mineral soils or boulders in tundra, mountain heaths or on higher hilltops.…”
Section: Discussionmentioning
confidence: 99%
“…First, many lichen-forming species reveal large and unexplained distribution patterns, such as various disjunct ranges [ 17 ]. One could thus expect significant geographic variation in lichen environments, favoring a diversity of responses through plasticity and acclimation [ 18 ], switching to alternative algal (phototroph) partners [ 19 , 20 ] or adaptive divergence [ 21 , 22 ]. At the same time, a scarcity of taxonomically useful morphological or chemical characters implies that many historically described lichen-forming species involve multiple evolutionary lineages that may be habitat specific and merit recognition as full species (e.g., [ 23 ]).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is widely acknowledged that specificity of the mycobiont-photobiont association as well as the spatial distribution of their component species largely drives the formation of new lichen organisms 6,[14][15][16] . Indeed, many symbionts are quite stringent in the partnerships they form, which are often determined by biophysical gradients [17][18][19][20][21][22] . It has also been suggested that highly specific mycobionts are typically restricted to few environments and display limited ecological range 23,24 .…”
Section: Introductionmentioning
confidence: 99%